Attenuation of rock blasting induced ground vibration in rock-soil interface - Jayasinghe, Bhagya (2020)
Blasting has been widely used in mining and construction industries for rock breaking. This paper presents the results of a series of field tests conducted to investigate the ground wave propagation through mixed geological media. The tests were conducted at a site in the northwestern part of Singapore composed of residual soil and granitic rock. The field test aims to provide measurement data to better understand the stress wave propagation in soil/rock and along their interface. Triaxial accelerometers were used for the free field vibration monitoring. The measured results are presented and discussed, and empirical formulae for predicting peak particle velocity (PPV) attenuation along the ground surface and in soil/rock were derived from the measured data. Also, the ground vibration attenuation across the soil-rock interface was carefully examined, and it was found that the PPV of ground vibration was decreased by 37.2% when it travels from rock to soil in the vertical direction.